The Capability of Hydrilla as a Phytoremediator for River Water - Asma Ali Moubark; Lukman Hakim; Amin Setyo Leksono (Graduate Program, 2018)
The aim of this study is to investigate the feasibility of Hydrilla as a phytoremediator to improve the quality of river water samples collected from Brantas River, Malang, Indonesia. The phytoremediation process is carried out in static river water samples, and the results show that Hydrilla is capable to augment the reduction the nitrite and ammonia content in the samples, while leaving nitrate and phosphate unaffected within the constraints of the study. Keywords: Ammonia, Hydrilla, Nitrite, Phytoremediation, River Water